Seasonality and ecology of living coccolithophores in E. Mediterranean coastal environments (Andros Island, Middle Aegean Sea) - Dimiza, M.,; Triantaphyllou, M.,; Dermitzakis, M.D., (Micropaleontology, 2008)
This study concerns the species composition and seasonality of extant coccolithophore communities in Eastern Mediterranean coastal environments and investigates their significance as environmental indicators. Water samples were collected during six one-day cruises carried out between 2001 and 2004, in two separate marine ecosystems (Gulfs of Korthi and Kastro, southeastern coast of Andros Island). High species diversities (65 species of heterococcolithophores and 45 species of holococcolithophores), associated with the dominant K-selected taxa, Rhabdosphaeraceae, and holococcolithophores, were recorded during summer whereas low diversities coupled with maximum concentration of cells and the predominance of r-selected species (Emiliania huxleyi) were observed during late autumn-early spring. The coccolithophores of the upper photic zone have been grouped into four distinct communities (Emiliania huxleyi group, Palusphaera vandelii group, Rhabdosphaera clavigera group and Helladosphaera cornifera group). A taxonomic study of the modern coccolithophores of Aegean Sea is presented. Several combination coccospheres of Algirosphaera robusta with Sphaerocalyptra quadridentata have been well documented, therefore their synonymy is proposed and the remaining species of Sphaerocalyptra have been transferred to the genus Holococcolithophora. One more holococcolith-heterococcolith association between Corisphaera sp. type A, Zygosphaera bannockii, Zygosphaera amoena and Syracosphaera bannockii is presented, recombining all taxa into Syracosphaera amoena comb. nov. A new species, Holococcolithophora kastriensis sp. nov. is described.